Role of External Audit and its Impact on Improving the Quality of Accounting Information–an Analytical Study in the Opinions of a Sample of Leaders in the IBN Majid General Company - Hayder Jerri Mohsin; Ahmed Mahdi Abdulkareem (HM Journals, 2022)
The research aims to identify Role External Auditing improvement The quality of accounting information in a companye General Ibn Majid,The researchers used the questionnaire as a main tool for data collection by selecting a random sample with a size of (100) Respondent with the aim of displaying and analyzing the responses of the sample members and their perceptions of the study variables and its sub-dimensions and testing the study hypotheses using descriptive and inferential statistics methods, as well as using personal interviews and field observations as auxiliary tools in data collection. The researcher relied on statistical programs (16).SPSS V.25; Excel V) in processing and analyzing data by using the most appropriate statistical methods.The researcher reached a number of results, the most important of which are having a relationship Effect And the link Between the independent variable, external audit and its dimensions(The importance of external audit for the organization, the effectiveness of the external auditor’s procedures In the organization, the means that contribute to the effectiveness of the external audit)The dependent variable is the quality of accounting information and its dimensions (efficiency of accounting information,Effectiveness of accounting information,The reliability of the accounting information).